PENGARUH WAKTU DAN SUHU PENYIMPANAN SAMPEL DARAH TERHADAP HASIL PEMERIKSAAN UJI SILANG SERASI (CROSS MATCH) - Anita Oktari; Linda Mulyati (Journal of Indonesian Medical Laboratory and Science, 2022)
Cross Match is an examination by reacting donor serum with patient cells (minor) and reacting patient serum with donor cells (major). Research has been carried out on the effect of time and temperature of storage of blood samples on the results of the Cross Match examination. The method used in this research is the gel test method. Blood samples were stored at refrigerator and room temperature with storage times of 0, 2nd, and 4th days. The results showed that there were differences in the quality of the results of the Cross Match examination on blood samples with storage times of 0, 2nd, and 4th days. The results of the Cross Match examinations at the refrigerator temperature for the 2nd and 4th days were the same as the control samples. The results of the Cross Match examinations at room temperature for the 2nd day were still the same as the control samples, while on the 4th day showed different results, namely there was agglutination accompanied by mixed fields on the results of the Major, Minor and Auto Control. Then the conclusions obtained are the time and temperature of storage of blood samples affect the results of the Cross Match examinations.